2014
DOI: 10.1680/si.13.00047
|View full text |Cite
|
Sign up to set email alerts
|

Hollow polysiloxane nanostructures based on pressure-induced film expansion

Abstract: IntroductionSuperhydrophobic surfaces comprise a class of materials characterized by extreme water repellency, a low roll-off angle and self-cleaning ability.1-5 These ultimate properties are achieved by combining roughness with a low-energy surface.1-3,6-9 The composite CassieBaxter wetting state 10 is connected to superhydrophobicity through high contact angles and low roll-off angles. Industrial applications concerning superhydrophobicity are currently only slightly behind the academic state-of-the-art, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
(70 reference statements)
0
9
1
Order By: Relevance
“…It is logical to conclude that the condensation between Si–OH/Al–OH existing on the surface of the geopolymer and PMHSO may always occur during the self-cross-linking of the PMHS to form silicone nanofilaments. This may be different from the previous view that the growth of the silicon nanofilaments is initiated by the tip. ,,,, The in situ growth of this silicon nanofilaments can be attributed to the root, which triggers the “mushroom like” strand to stretch upwards successively to form the final one-dimensional nanostructure.…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…It is logical to conclude that the condensation between Si–OH/Al–OH existing on the surface of the geopolymer and PMHSO may always occur during the self-cross-linking of the PMHS to form silicone nanofilaments. This may be different from the previous view that the growth of the silicon nanofilaments is initiated by the tip. ,,,, The in situ growth of this silicon nanofilaments can be attributed to the root, which triggers the “mushroom like” strand to stretch upwards successively to form the final one-dimensional nanostructure.…”
Section: Resultscontrasting
confidence: 60%
“…From this, one-dimensional soft matter, silicone nanofilaments (SNFs), with unusual wetting behavior is derived. These were first synthesized through chemical vapor deposition and liquid deposition by Gao and McCarthy using methyltrichlorosilane and vapor-phase plasma-induced polymerization using vinyltrichlorosilane by Rollings et al Currently, these have been prepared on the surfaces of glass, ceramics, cotton fabric, silk, wood, nanofibrillated cellulose, etc. ,, In addition to excellent hydrophobicity, they exhibit high transparency, environmental stability, good solvent resistance, and chemical resistance over a certain range. Up to now, the preparation technology of silicone nanofilaments is still based on vapor-phase and liquid-phase depositions mainly, , and only a few changes or improvements on this basis have been found in the follow-up study. , There is no exception that the relationship between the formation of a filamentous structure and the film water layer enriched on the surface of the substrate was emphasized in these publications. Proper control of the humid environment and reasonable dosage of silane had always occupied the core of the research on these materials. ,,,,, Recently, a droplet-assisted growth and shaping mechanism has been proposed to explain the in situ formation of nano- and microstructures composed of polysiloxane and other materials such as germanium oxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface was prepared as described in the literature 34 . Silicon (100) wafer was cleaned by ultrasonication in alkaline solvent (Deconex 11 Universal, VWR), rinsed thoroughly by Milli-Q water, and dried under nitrogen flow.…”
Section: Methodsmentioning
confidence: 99%
“… 21 Such features were reported earlier for other systems. 27 , 28 For instance, a study dealing with the superhydrophobization of textile materials with TC indicated the appearance of hairy features, therein described as nanofilaments. 27 Within a different scope, Korhonen et al 28 implemented a controlled system to grow hollow polysiloxane nanofilaments from silicon wafer surfaces using TC as the precursor and provided detailed insight into the growing mechanisms.…”
Section: Resultsmentioning
confidence: 99%